Co-distribution, possible origins, status and potential health risk of trace elements in surface water sources from six major river basins, Bangladesh. (June 2020) - Islam, Abu Reza Md Towfiqul; Islam, H.M. Touhidul; Mia, Md Uzzal; Khan, Rahat; Habib, Md Ahosan; Bodrud-Doza, Md; Siddique, Md Abu Bakar; Chu, Ronghao
Abstract: In this study, we appraised the concentrations of 8 major trace elements (TEs) in surface water sources from six river basins, Bangladesh: Meghna, Kartoya, Sitalakha, Teesta, Pashur and Rupsha River basins. Co-distribution, the status of water quality and potential health risks were assessed using statistical analyses, the entropy water quality index (EWQI), sodium adsorption ratio (SAR), spatial autocorrelation index (SAI), hazard index (HI), and Monte-Carlo (MC) simulation. The spatial variations of TEs concentrations differed notably among the studied river basins. The average concentrations of TEs (except Ni, As, and Zn) in six river basins exceeded the drinking water quality guidelines. About 20% of water samples in six basins were categorized as undrinkable to poor qualities for drinking uses, while good water quality for irrigation purposes. The entropy theory identified that Cr, Pb, and As are the key pollutants influencing the water quality. According to the results of non-carcinogenic risk, the hazard index (HI) values for adults and children surpassed the allowable limit (>1), demonstrating detrimental health effects on humans. The carcinogenic risk values of chromium (Cr) were much higher than As and Cd exposures which exceeded the benchmark recommended by US EPA (>10 −6 to 10 −4 ), with an elevated risk for adults than children through the oral intake as the primary exposure route. Overall, the results suggest that the local population exposed to surface water may pose an adverse health effect, thus, strict regulation and efficient management should be focused on Cr, Cd and As monitoring and appraisal in these basins. Graphical abstract: Image 1 Highlights: Co-distribution, and potential health risks of trace elements (TEs) were assessed in six river basins. Cr, Pb, and As are the main pollutants influencing the water quality. Hotspots of TEs contents were linked to the existence of industrial and urban runoff as the key contamination source. Local population exposure to TEs polluted water poses adverse health impacts.